Identifying Purine Intake Among People with Gout and Its Relationship with Uric Acid Level: A Cross-Sectional Study - Yusron Amin; Haswita Haswita; Sephya Nola Tiarasari (International Journal of Advanced Health Science and Technology, 2025)
Gout was still one of the chronic disease trends suffered by the community which was characterised by elevated uric acid levels. This condition is closely related to lifestyle, namely the consumption of purine-rich foods. However, there were not studies that discovered the relationship between purine-rich food intake with elevated uric acid levels. This study aims to analyse the relationship between purine-rich food intake with elevated uric acid levels. This study used a correlational design with a cross-sectional approach. The population was the community in village "x" who suffered from gout with a total of 70 people. From them, 66 people were selected as participants who met the inclusion criteria through a purposive sampling method. The instrument used was a questionnaire for the variable of purine-rich food intake and uric acid test with a GCU meter. The results showed that there was a strong positive correlation between purine-rich food intake with elevated uric acid levels (p = 0,000; r = 0,567), this is evidenced by the fact that the majority of participants with high uric acid levels had a history of consuming purine-rich foods exceeding the daily tolerance limit, whereas low or normal uric acid levels were found in participants with a history of consuming high purine foods below the threshold or even not consuming purine-rich foods. These results indicated that consuming purine-rich foods could have a significant impact on elevated uric acid levels, so it was necessary to reduce or limit daily purine food intake.